Analisis Tindak Tutur Lokusi, Ilokusi dan Perlokusi Dalam Acara Podcast Log In X Close The Door - Nur Lenasari (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study is motivated by speech acts in internal language podcast Habib Husein Ja'far, Onadio Leonard, and Steve Marcel entitled " Perang Takjil, Nanti Paskah Kami Balas Kalian!". A speech act is an activity of saying something. Locutionary speech acts are speech acts that express something in the sense of "saying" or speech acts in the form of sentences that are meaningful and understandable, while illocutionary speech acts are speech acts that are usually identified with explicit performative sentences, perlocutionary speech acts are the impact caused by speech to the speaker, so that the speaker takes action based on the speaker. The aim of this study is to determine the use of speech acts in language, namely locutionary, illocutionary and perlocutionary acts in podcast Habib Husein Ja'far. The theory used is pragmatic theory. Pragmatic theory is a science that studies the use of language which is linked to the context of its use. The research method used is a qualitative descriptive method, the data source in this research is video podcast Habib Husein Ja'far. Based on the results of the discussion, the researcher found that there is the use of speech acts in internal language podcast Habib Husein Ja'far there are locutionary, illocutionary and perlocutionary speech acts.